Research on Temporal and Spatial Evolution of Habitat Quality and Terrain Gradient Effect in Hilly Areas: A Case Study of Changsha-Zhuzhou-Xiangtan Urban Cluster - Huang, Shuqi; Wen, Yujing (International Journal of Natural Resources and Environmental Studies, 2024)
Habitat quality is an important manifestation of the service functions and biodiversity in an ecological service system. Hilly areas have complex terrain and sensitive and diverse ecological environment characteristics. This study describes the spatiotemporal evolution of habitat quality in the Changsha-Zhuzhou-Xiangtan urban cluster from 2010 to 2020 based on the InVEST model, and explores its spatial differentiation and change characteristics under different topographic gradients. The results show that the habitat quality in the Changsha-Zhuzhou-Xiangtan urban cluster is showing a downward trend, with a spatial pattern of ‘middle loss and high, surrounding loss low’, and has obvious spatial cluster characteristics. The habitat quality in areas with a topographic gradient of 1 is the worst, while the habitat quality in areas with a topographic gradient of 5 is the best. The habitat quality and topographic gradient show a positive growth trend. Based on the investigation of the spatio-temporal evolution characteristics of the habitat quality in the Changsha-Zhuzhou-Xiangtan urban cluster and the effect of topographic gradient, it provides a theoretical basis and scientific basis for the protection of ecological space and the optimization of the spatial structure of land use in hilly areas, which is of great significance for promoting the sustainable ecological development of hilly urban clusters.